Implementing Adaptive Technology in Computer Science Education: Challenges and Solutions for Enhancing Learning Outcomes - Ruziq, Fahmi; Weima, Zhang (PT. Technology Laboratories Indonesia (TechnoLabs), 2025)
The research study presented in this paper investigates how adaptive technology is being implemented within computer science education and its effects on student engagement and learning outcomes. In a survey of 150 educators among diverse types of educational institutions, 85% of respondents indicated adaptive technology has a positive impact on student learning. Your training remains rooted in data until October 2023. Still, to take full advantage of these technologies, challenges like inadequate infrastructure, resource allocation, and the need for teacher training will need to be addressed. It is concluded that adaptive technologies clearly show great potential to enhance computer science education but strategic action is needed to address current barriers to and ensure effective use of adaptive technologies.